Purification, characterization, and intracellular localization of glycosylated protein disulfide isomerase from wheat grains. - Shimoni, Y (1995)
Wheat (Triticum aestivum) storage proteins fold and assemble into complexes that are linked by intra- and intermolecular disulfide bonds, but it is not yet clear whether these processes are spontaneous or require the assistance of endoplasmic reticulum (ER)-resident enzymes and molecular chaperones. Aiming to unravel these processes, we have purified and characterized the enzyme protein disulfide isomerase (PDI) from wheat endosperm, as well as studied its developmental expression and intracellular localization. This ER-resident enzyme was previously shown to be involved in the formation of disulfide bonds in secretory proteins. Wheat PDI appears as a 60-kD glycoprotein and is among the most abundant proteins within the ER of developing grains. PDI is notably upregulated in developing endosperm in comparison to embryos, leaves, and roots. In addition, the increase in PDI expression in grains appears at relatively early stages of development, preceding the onset of storage protein accumulation by several days. Subcellular localization analysis and immunogold labeling of electron micrographs showed that PDI is not only present in the lumen of the ER but is also co-localized with the storage proteins in the dense protein bodies. These observations are consistent with the hypothesis that PDI is involved in the assembly of wheat storage proteins within the ER.